2021
DOI: 10.24093/awej/vol12no2.2
|View full text |Cite
|
Sign up to set email alerts
|

English As Secondary Language Learning and Autism Spectrum Disorder: The Obstacles in Teaching and Learning the Language

Abstract: To this date, there has been an increasing number of children across the globe diagnosed with an autism spectrum disorder. There has been much literature that discussed the issues and obstacles common learners face in their English language learning journey. Yet, not much spotlight and acknowledgment were given to the learners with Autism in their voyage of English language learning. In conjunction to that, this paper intends to investigate the obstacles that the learners with Autism face in their English as s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In their study, Hashim, Yunus, and Norman (2021) have proven that children with autism indeed encounter challenges and issues in their language learning journey. Due to their different behaviors and characteristics, teachers sometimes struggle to try to personalize the learning materials for them.…”
Section: Discussionmentioning
confidence: 98%
“…In their study, Hashim, Yunus, and Norman (2021) have proven that children with autism indeed encounter challenges and issues in their language learning journey. Due to their different behaviors and characteristics, teachers sometimes struggle to try to personalize the learning materials for them.…”
Section: Discussionmentioning
confidence: 98%
“…Their tendency to systemise may help them with learning word parts, creating groups of words and learning multi-word units, all of which are of key importance according to Nation (2022) and Web and Nation (2017). In addition to this, Hashim et al (2021) state that autistic children's learning English is faster than learning L1 in certain cases. They link it to specific characteristics of the English language itself.…”
Section: The World Of People On the Autism Spectrummentioning
confidence: 99%
“…With regards to the second/foreign language (L2) learning context, learners with ASD seemed to face doubled challenges as they need to learn an L2 even when they may struggle to communicate in their first language or mother tongue (L1) (Barletta, 2018). A recent study in Malaysia by Hashim et al (2021) reported several obstacles faced by young autistic learners of English such as difficulty in learning new vocabulary, in responding to and initiating interactions, further hampering the learning process. However, Hashim et al (2021) also highlighted the crucial roles teachers play in facilitating learners with ASD to learn an L2.…”
mentioning
confidence: 99%
“…A recent study in Malaysia by Hashim et al (2021) reported several obstacles faced by young autistic learners of English such as difficulty in learning new vocabulary, in responding to and initiating interactions, further hampering the learning process. However, Hashim et al (2021) also highlighted the crucial roles teachers play in facilitating learners with ASD to learn an L2. An example of the important role of a teacher to help learners with ASD could be seen from a study conducted by Zohoorian et al (2021) involving two learners with ASD, one with a moderate spectrum and the other one with a severe spectrum.…”
mentioning
confidence: 99%